The end of alternatives? Capitalist transformation, rural activism and the politics of possibility in China†. Issue 7 (10th November 2018) - Day, Alexander F.; Schneider, Mindi
ABSTRACT: This paper examines the politics of possibility for rural activism in reform era China. By periodizing rural reforms from 1990, we explore the political-economic changes that have coalesced in the reform era, and how these changes condition forms and possibilities of activism. We argue that the current modernization–urbanization drive that emerged around 2008 is foreclosing opportunities for the pro-peasant cooperative forms that New Rural Reconstruction activists imagined earlier in the decade. Instead, as the process of capitalist agrarian change deepens in the countryside, food- and farming-related activism now resembles the state's focus on markets and consumption, to the detriment of addressing social relations of production. Without a focus on distributional politics and power, this shift has the potential to further entrench existing inequalities within and across rural and urban spaces. The contextual work undertaken in this paper is currently absent from the emerging literature on China's agrifood transformations.